PENGARUH VASEKTOMI TERHADAP FUNGSI SEKSUAL PRIA - Fitri, Mir'atul; Wantouw, Benny; Tendean, Lydia (Universitas Sam Ratulangi, 2013)
Abstract: Vasectomy in the community are still poorly understood, such as vasectomy can affect sexual function (sexual dysfunction). The purpose of this study was to determine the effect of vasectomy on male sexual function and the mechanisms of sexual function in men due to vasectomy. This study is a cross sectional analytic survey with a target population of men who have vasectomy totaling 67 people selected by proportional sampling of Manado City BKKBN January to August 2012. Instruments in this study using the questionnaire International Index Erectile Function (IIEF), the analysis of the data in this study using univariate analysis and Mann Whitney Sub Menu 2 Independent simple (SPSS 20 for Windows). The results, the majority of respondents aged > 35 years were 63 people (94.03%), elementary education as many as 48 people (62.34%), earning Rp. 500,000 - Rp. 1.000.000 by 47 people (70.1%), having more than one child as many as 64 people (95.5%), vasectomy contraceptive users with better sexual function by 56 people (83.60%), significant results statistics between vasectomy contraceptive users who have comorbidities, consuming drugs and having stress with sexual function. Contraception has no effect on male sexual function and sexual dysfunction occurs due to men having comorbidities, smoking and excessive alkohol consuming in the long term, drug users, and have excessive stress. Keywords: Vasectomy, Sexual Function, Male. ABSTRAK: Vasektomi dikalangan masyarakat masih kurang dipahami, seperti vasektomi dapat berdampak terhadap fungsi seksual (disfungsi seksual). Tujuan penelitian ini untuk mengetahui pengaruh vasektomi terhadap fungsi seksual pria dan mekanisme fungsi seksual pada pria akibat vasektomi. Penelitian ini bersifat survei analitik pendekatan cross sectional dengan populasi target pria yang telah divasektomi berjumlah 67 orang dipilih secara proporsional sampling dari data BKKBN Kota Manado Januari-Agustus 2012. Instrumen dalam penelitian ini menggunakan Kuesioner Indeks Fungsi Ereksi Internasional (IIEF), analisa data dalam penelitian ini menggunakan analisa univariat dan analisa Mann Whitney Sub Menu 2 Independent simple (SPSS 20 for Windows). Hasil penelitian didapatkan mayoritas responden usia >35 tahun sebanyak 63 orang (94,03%), berpendidikan SD sebanyak 48 orang (62,34%), berpenghasilan Rp. 500.000 – Rp. 1.000.000 sebanyak 47 orang (70,1%), memiliki anak lebih dari satu orang sebanyak 64 orang (95,5%), pengguna kontrasepsi vasektomi dengan fungsi seksual baik sebanyak 56 orang (83,60%), hasil yang bermakna secara statistik antara pengguna kontrasepsi vasektomi yang memiliki penyakit penyerta, mengkonsumsi narkoba dan mengalami stres dengan fungsi seksual. Kontrasepsi vasektomi tidak berpengaruh pada fungsi seksual pria dan disfungsi seksual terjadi diakibatkan oleh pria memiliki penyakit penyerta, merokok dan mengkonsumsi alhokol dalam jangka waktu panjang dan volume berlebihan, pengguna narkoba, dan memiliki stress berlebihan. Kata kunci: Vasektomi, Fungsi seksual, Pria.